Trypanotolerant livestock in West and Central Africa. Volume 2. Country studies -Chapter 3. Guinea Bissau - International Livestock Centre for Africa (International Livestock Centre for Africa, 1980)
Data on livestock census & distribution, productivity estimates for N'Dama cattle, and herd composition and management, with note on research centres and development projects.